Optimization of enzymatic hydrolysis conditions of chemical pretreated cotton stalk using response surface methodology for enhanced bioethanol production yield - Yildirim, Oznur; Tunay, Dogukan; Ozkaya, Bestami (SPRINGER HEIDELBERG, 2023)
Lignocellulosic biomass is a promising biofuel source that is studied for recent years. However, the biofuel potential of lignocellulosic biomass relies on the pretreatment performance directly and sugar recovery yields, and the pretreatment processes required to achieve that yield are significant. Therefore, several pretreatment methods (acid, alkaline, liquid hot water, and enzymatic hydrolysis) were investigated in different conditions (temperature, enzyme load, and duration) to determine mathematically and statistically best conditions. In the results obtained from this study, acid pretreatment (2% v/v) had the highest effect for obtaining reducing sugar from cellulose, hemicellulose, and lignin compared to liquid hot water (150 degrees C) and base (0.75% w/v) pretreatments from cotton stalk. According to the response surface methodology analysis, the most efficient achievable enzymatic hydrolysis load was 40 FPU/g biomass with 65-h retention time in 45 degrees C. The highest total reducing sugar yield was found as 30 g fermentable sugar/L or 0.36 g sugar/g biomass, and the bioethanol concentration was found as 9.5 g/L.
Keywords: Lignocellulosic biomass; Pretreatment; Enzymatic hydrolysis; Response surface methodology; Bioethanol; ETHANOL-PRODUCTION; RICE STRAW; ACID; SACCHARIFICATION; DETOXIFICATION; CELLULASE; ENERGY; Energy & Fuels; Engineering